Efficacy of local and systemic corticosteroid and hyaluronidase therapy in oral submucous fibrosis: a histopathological study - Bansal, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: As the etiopathogenesis of OSMF is not well established, a myriad of different medical and surgical modalities of treatment are reported however studies on histopatholgical changes after treatment are very sparse. There are reports on various regimens of steroids using different molecules, doses and routes of administration and their combination with other drugs. These were the driving factors to conduct this study. This histopathological study was conducted to know the efficacy of various forms of steroid therapy in various combinations. Methods: This prospective randomized single blinded outcome based study was conducted in the department of Otorhinolaryngology (ENT) and Pathology in a tertiary care medical college hospital. The 150 clinically diagnosed patients were divided into 5 groups: A, B, C, D and E. Each group was treated differently with different modes of administration of steroids with and without combinations of other medicines. To study histopathological changes before and after treatment, biopsy was taken in 100 patients who gave their consent for the same. Results: The various histopathological changes observed in the tissues taken after the treatment in 100 patients, were in terms of changes in the epithelium towards normalisation, decrease in fibrous tissue in the submucosa, decrease in the cellular infiltration, appearance of new capillaries, restoration of glandular activity and decrease in the fibrosis of muscles. The calculated Chi square value (p>0.05) was found less than table value. Conclusions: Local and systemic corticosteroid and hyaluronidase therapy in patients with OSMF were found effective. However, histopathologically, it was not found statistically significant whether corticosteroids are given locally and/or systemic with or without injection hyaluronidase.